Senior Cohousing: The Social Architecture of Cohousing, Community Design & Well Being - (:unkn) unknown (My University, 2021)
The world is facing a situation without precedent, due to the anticipated growth in and increasing longevity of elderly people. Where and how people live is and can be a determinant of health. There is substantial research on inadequate housing for older people and its adverse effects on health. However, less is known about how senior cohousing affects the health of its residents. Further research is needed to improve strategies for senior living environments that promote social interaction and facilitate well-being. This study aims to bolster design and policy strategies by investigating how senior cohousing residents perceive how their living situation affects their well-being. The theoretical underpinning for this study brings together the aging theories together with Rowe and Kahn’s (Rowe & Kahn 1997, 2015) and Baltes’ (Baltes & Baltes, 1990), theories on successful aging and well-being. These approaches expand on the Person (PE)-Environment dynamic interchange while adding Socialization (S) into the models’ framework the complex blending of physiological, behavioral, and social interaction that occur at scales of the individual, built environment, and community. This research investigates how environmental design and improved social networks result in measurable improvements in quality of life (QOL), life satisfaction (LS), and well-being (WB). The study sought to evaluate the determinants across multiple SR (self-reported) measures of health. The survey results show that increased are statistically significant for QOL, LS, and WB. Senior cohousing residents are a select group of individuals who seek a more meaningful and socially connected life. They enjoy independence, autonomy, and a healthier, active aging process. The research shows that high-quality social interaction and sustainable and environmentally sensitive architectural design, through the concept of Socially Enriched Environments (SEE) and Nature Rich Environments (NRE), promote a positive sense of well-being, and self-rated health (SRH). Senior cohousing is a necessary consideration for policy initiatives in the United States, given current health care cost trajectories for the aged which are unsustainable. If undertaken, this typology can potentially relieve some of the associated costs of providing health care. It has the clear potential to help relieve social isolation and lack of social support. However, currently, the domestic senior cohousing cohort is a highly selective group with substantial life resources (education, income, assets, and resilience) that puts them well outside normal population distributions in the U.S. Meanwhile, senior cohousing has and is becoming a well-established typology. Meanwhile, senior cohousing has and is becoming a well-established typology in Denmark, Sweden, and, more recently, the United Kingdom. The establishment of these European communities relies on policy initiatives and organizational and financial assistance which make it a viable option. In the U.S., the provision of policy assistance in the formation of senior cohousing communities can reduce the amount of lead time necessary to develop these communities and the high costs of initial development while potentially increasing the number of seniors who could live in them.
Keywords: Cohousing; Community Design; Cooperative Housing; Gerontology; Social Capital; Successful Aging